2001
DOI: 10.1149/1.1357316
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Electrochemical Windows of Aprotic Alkali Metal (Li, Na, K) Salt Solutions

Abstract: This work is a comparative study of the electrochemical windows and the basic processes on gold electrodes in LiClO 4 , NaClO 4 , and KClO 4 solutions in propylene carbonate ͑PC͒. The analytical tools included cyclic voltammetry, electrochemical quartz crystal microbalance, surface-sensitive Fourier transform infrared spectroscopy ͑ex situ, external reflectance mode͒, and X-ray photoelectron spectroscopy. The apparent electrochemical windows of these systems are anodically limited at potentials above 1.3 V ͑vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
181
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(194 citation statements)
references
References 23 publications
11
181
0
Order By: Relevance
“…Their recent studies revealed that traces of oxygen, water and PC-reduction products form passivating surface films on gold, platinum, silver, nickel and copper electrodes, when these are polarized to low potentials in lithium-salt solutions. 53 In the study it was also found that the major constituent in the surface films is the PC-reduction product, CH 3 CH(OCO 2 2 Li surface species by LiF. The author concluded that it is not an increase in the SEI thickness, but rather resistivity changes that contribute to species-controlled resistance and lead to the high interfacial impedance of the lithium anode in LiPF 6 and LiAsF 6 electrolytes.…”
Section: Chemical Composition and Properties Of The Sei On Inert Subsmentioning
confidence: 94%
“…Their recent studies revealed that traces of oxygen, water and PC-reduction products form passivating surface films on gold, platinum, silver, nickel and copper electrodes, when these are polarized to low potentials in lithium-salt solutions. 53 In the study it was also found that the major constituent in the surface films is the PC-reduction product, CH 3 CH(OCO 2 2 Li surface species by LiF. The author concluded that it is not an increase in the SEI thickness, but rather resistivity changes that contribute to species-controlled resistance and lead to the high interfacial impedance of the lithium anode in LiPF 6 and LiAsF 6 electrolytes.…”
Section: Chemical Composition and Properties Of The Sei On Inert Subsmentioning
confidence: 94%
“…A possible reason could be nested in the high solubility of the sodium oxides and carbonates in PC [36] due to the mild Lewis acid character of Na. This could result in the formation of less dense SEI films in PC-based electrolytes as 7 observed previously by SEM.…”
Section: Submitted To 4mentioning
confidence: 99%
“…The milder Lewis acid character of Na as compared to Li, which we could first see as a positive asset, turns out to be detrimental since most of the Nabased species forming the SEI are more soluble, hence leading to a less passivating SEI. 5 Fundamental mastery of SEI formation is greatly needed; the absence of such understanding can easily mislead us when testing new materials in Na half-cells. Gladly such an issue is alleviated by replacing Na by carbon in full Na-ion coin cells.…”
mentioning
confidence: 99%